Umbilical artery Doppler velocimetry study on prediction of adverse pregnancy outcomes among pregnant women with hypertensive disorders in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Doppler velocimetry studies have been widely used to predict adverse pregnancy outcomes in hypertensive disorders of pregnancies.Objective:To identify the pregnant women with hypertensive disorders for umbilical artery Doppler velocimetry to predict adverse pregnancy outcomes.Methods:This was a prospective study among 264 pregnant women with hypertensive disorders. The umbilical artery Doppler velocimetry study was conducted using 3.5 m Hz convex of the Mindry Digital Ultrasound Imaging System (Model DP-8800Plus; Shenzen Mindray Biomed Electronics, China).Results:A total of 264 pregnant women within the age of 18–40 years with a mean ± standard deviation of 31.33 ± 5.92 were studied. One hundred and twenty-four (29.90%) presented with pregnancy-induced hypertension (PIH), 72 (58.06%) had abnormal resistive indices (RIs) of at least 0.58 of which 4 had diastolic notches. The remaining 52 (41.94%) had normal RIs with no diastolic notch. Twenty (4.80%) presented with preeclampsia, 12 (60.00%) had abnormal RI of which four had diastolic notches. One hundred and twenty (28.90%) women presented with chronic hypertension, 72 (60.00%) had abnormal RI of which 16 had diastolic notches. Abnormal RI was associated with low Apgar scores and early neonatal death among the patients with PIH, low Apgar scores among patients with preeclampsia and low birth weight among chronic hypertensive pregnant women.Conclusion:We found abnormal umbilical artery Doppler velocimetry RI to be associated with adverse pregnancy outcomes. However, diverse nature of the hypertensive disorders and adverse pregnancy outcomes revealed different optimum cut-off points for various hypertensive disorders following ROC analysis.